Click, Clack, Peep! - Cronin, Doreen; Lewin, Betsy (New York Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2015)
All of the barnyard animals are excited about the arrival of a new duckling, until the noisy little one refuses to go to sleep.
Keywords: Domestic animals -- Juvenile fiction; Ducks -- Juvenile fiction; Animals -- Juvenile fiction -- Infancy; Sleep -- Juvenile fiction; Domestic animals -- Fiction; Ducks -- Fiction; Animals -- Fiction -- Infancy; Sleep -- Fiction; Humorous Stories